The common glue : an alternative way of transcending differences to unleash competitive performance - Morosini, Piero (International business and management series., 2005)
Presents an evidence on what drives the competitive performance of organizations in the multicultural milieu. This evidence suggests that only when an organization develops a strong ""Common Glue"" that blends its male and female characteristics at the leadership levels, does it become capable of transcending cultural, and geographic boundaries.